2017
DOI: 10.1002/ijc.30929
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of transforming growth factor‐β signaling enhances oncolytic herpes simplex virus efficacy in patient‐derived recurrent glioblastoma models

Abstract: Despite the current standard of multimodal management, glioblastoma (GBM) inevitably recurs and effective therapy is not available for recurrent disease. A subset of tumor cells with stem-like properties, termed GBM stem-like cells (GSCs), are considered to play a role in tumor relapse. Although oncolytic herpes simplex virus (oHSV) is a promising therapeutic for GBM, its efficacy against recurrent GBM is incompletely characterized. Transforming growth factor beta (TGF-β) plays vital roles in maintaining GSC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…Alternatively, EMT could contribute to the acquired resistance to EGFR inhibitors as implicated in lung cancer 18 . Indeed, we did observe increased expression of representative mesenchymal markers in the post-dacomitinib tumours, both in the patient and in the xenografts, as seen with other recurrent GSC xenografts 39 . Further study is necessary to determine whether an EMT-like phenomenon observed in relapsed glioblastoma is associated with resistance to targeted therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Alternatively, EMT could contribute to the acquired resistance to EGFR inhibitors as implicated in lung cancer 18 . Indeed, we did observe increased expression of representative mesenchymal markers in the post-dacomitinib tumours, both in the patient and in the xenografts, as seen with other recurrent GSC xenografts 39 . Further study is necessary to determine whether an EMT-like phenomenon observed in relapsed glioblastoma is associated with resistance to targeted therapy.…”
Section: Discussionsupporting
confidence: 63%
“…However, we all have recognized that OHSV expression of IL-12 and its application as a monotherapy does not provide a desired therapeutic outcome, as demonstrated in several preclinical cancer models [30,84,86,148,149]. It requires synergistic or additive combination approach with other anti-cancer therapies for an improved therapeutic outcome [19,25,76,148,150,151]. Similar to OHSV-IL12, a combination immunotherapeutic approach is also required to enhance anti-tumor efficacy of other OVs encoding IL-12 [49,134,136,138,139].…”
Section: Discussionmentioning
confidence: 99%
“…To passage cells, neurospheres were dissociated with the NeuroCult Chemical Dissociation Kit (StemCell Technologies). These GSCs (not all for each feature) have been characterized by us and other investigators for sphere-forming ability and tumorigenicity 10,13,14,21,61 , epigenetic and genetic alterations 10,14,21,61,62 , gene expression and subtype classification 14,61,62 , and in vitro self-renewal 13,14,61,63 and differentiation 13,14,62 . ScGCs from the same tumor specimens as GSCs were isolated as described 13 , and grown in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal calf serum (FCS).…”
Section: Methodsmentioning
confidence: 99%